Penyuluhan Bahaya Narkotika terhadap Masyarakat dari Perspektif Kesehatan, Pencegahan, dan Penegakan Hukum di Desa Cipambuan, Bogor. - Alvianto, Danang; Afriansyah , Ryan; Rahmawati, Vina; Bagus Setiawan, Anggie; Sukmana Putri, Sarah Ayu Ramadhani; Syahdan, Syahdan; H , Dasril; Pawoko, Akbar Maulana; Labib, M Ichawn; Saputri, Karina; Almusa, Aldi; Suhendry, Reno; Sutrisno, Andri (Jurnal Pengabdian Kepada Masyarakat, 2025)
This journal discusses a collaborative effort in addressing the issue of narcotics abuse from the perspectives of health, prevention, and law enforcement. The program was implemented through a community service initiative in Cipambuan Village, Bogor, involving legal scholars, students, and practitioners who joined forces to provide public education. Two expert speakers from BNNK Bogor and the Police offered crucial insights into the health and legal aspects of narcotics abuse. The health component emphasized the protective role of family religiosity and harmony, while also warning about the emergence of new addictive substances in disguised forms, such as candy and snacks. These findings show that family-based prevention is an effective strategy when combined with consistent community education. On the legal side, the Police emphasized the importance of law enforcement in rural areas and encouraged community vigilance against illegal drug circulation. The synergy of these perspectives highlights the significance of preventive education and cooperative enforcement. The study demonstrates how students, through community service programs, act as agents of change by bridging academic knowledge with real-world societal issues. Moreover, the program embodies the spirit of tridharma education, research, and community service by creating sustainable collaborations between educational institutions, local communities, and government stakeholders. This integrated approach is essential to protect younger generations from the ever-evolving threats of narcotics.